Studi Kehidupan Anak Korban Pandemi Covid-19 di Kabupaten Purbalingga - Pingkan Zahra Azizah; Nanang Martono; Sulyana Dadan; Ankarlina Pandu Primadata; Tyas Retno Wulan (Jayapangus Press, 2023)
Children become one of susceptible groups who get the risks during pandemic period. The risks can be the threat of exposure up to losing their parents who passed away because of Covid-19. The children who lose their parents due to Covid-19 are susceptible to have the problems of health, economy, education guarantee, violence, and other human rights violations. They need social protection to help their growth and development into adulthood. The purpose of this writing is to describe the social condition and the problems of children who become the Covid-19 pandemic victims. They are fatherless kids, motherless children, or orphans whose parents passed away because of Covid-19. This research uses a quantitative research method (survey). The research data are taken by using questionnaires. The samples of this research are 124 or 32% of the children’s total number in Purbalingga Regency whose parents passed away due to Covid-19. The data are presented by using a frequency distributive table. The results show that most of the children are from the lower middle class family. After their parents passed away, the social economy condition of their family gets worse. It causes those children to face economic issues, so they are not able to pay their school fee. Therefore, there must be a social protection for them so that their rights as children are fulfilled.